Energy Balance of Puffing and Microexplosion of Two-Liquid Droplets; Fluid Dynamics; Vol. 59, iss. 6 - Antonov D. V. Dmitry Vladimirovich; Fedorenko R. M. Roman Mikhaylovich; Kovalev D. N. Dmitry Nikolaevich; Strizhak P. A. Pavel Alexandrovich (2024, 2024)
Title screen